2019
DOI: 10.1101/560730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Task-evoked activity quenches neural correlations and variability across cortical areas

Abstract: Many large-scale functional connectivity studies have emphasized the importance of communication through increased inter-region correlations during task states. In contrast, local circuit studies have demonstrated that task states primarily reduce correlations among pairs of neurons, likely enhancing their information coding by suppressing shared spontaneous activity.Here we sought to adjudicate between these conflicting perspectives, assessing whether co-active brain regions during task states tend to increas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 75 publications
(126 reference statements)
12
65
0
Order By: Relevance
“…Given the complex nature of subsequent analyses (i.e., network metrics) we chose this method of FC estimation for simplicity and wide-reaching comprehension. In the present study, connectivity estimates tended to decrease from rest to task, a finding that has been observed across numerous prior studies (that utilized various model species and neural recording methods) (Cohen and Maunsell, 2009;He, 2013;Cole et al, 2014;Ponce-Alvarez et al, 2015) and has well-founded neural mechanisms (Ito et al, 2019).…”
Section: Functional Connectivity Estimationsupporting
confidence: 84%
“…Given the complex nature of subsequent analyses (i.e., network metrics) we chose this method of FC estimation for simplicity and wide-reaching comprehension. In the present study, connectivity estimates tended to decrease from rest to task, a finding that has been observed across numerous prior studies (that utilized various model species and neural recording methods) (Cohen and Maunsell, 2009;He, 2013;Cole et al, 2014;Ponce-Alvarez et al, 2015) and has well-founded neural mechanisms (Ito et al, 2019).…”
Section: Functional Connectivity Estimationsupporting
confidence: 84%
“…Previous studies have shown that task-evoked coactivation might induce an inflation effect on estimates of intrinsic functional connectivity (Duff et al, 2018). As such, stimulus-evoked activity is suggested to clean up the 'background connectivity' in the task paradigm with a focus on intrinsic FC (Fair et al, 2007;Ito et al, 2019;Lurie et al, 2020;Norman-Haignere et al, 2012). Of note, our study also examined the functional connectivity using partial correlation.…”
Section: Discussionmentioning
confidence: 96%
“…For the pseudo-empirical simulations described above and for the empirical analysis we use fMRI resting state data from a pool of 100 random subjects from the minimally preprocessed HCP 1200 release , with additional preprocessing following Ito et al (2019) and Ciric et al (2017) . HCP data was collected in a 3T Siemens Skyra with TR = 0.72 s, 72 slices and 2.0 mm isotropic voxels.…”
Section: Empirical Fmri Analysis Methodsmentioning
confidence: 99%
“…Finally, the time series of the 360 regions were individually standardized to bring them to the same scale with mean 0 and standard deviation 1. Specific details about the nuisance regression are in Ito et al (2019) .…”
Section: Empirical Fmri Analysis Methodsmentioning
confidence: 99%